Etanercept in Alzheimer disease. (26th May 2015) - Butchart, Joseph; Brook, Laura; Hopkins, Vivienne; Teeling, Jessica; Püntener, Ursula; Culliford, David; Sharples, Richard; Sharif, Saif; McFarlane, Brady; Raybould, Rachel; Thomas, Rhodri; Passmore, Peter; et al.
<x xml:space="preserve">Abstract</x> Objectives: To determine whether the tumor necrosis factor α inhibitor etanercept is well tolerated and obtain preliminary data on its safety in Alzheimer disease dementia. Methods: In a double-blind study, patients with mild to moderate Alzheimer disease dementia were randomized (1:1) to subcutaneous etanercept (50 mg) once weekly or identical placebo over a 24-week period. Tolerability and safety of this medication was recorded including secondary outcomes of cognition, global function, behavior, and systemic cytokine levels at baseline, 12 weeks, 24 weeks, and following a 4-week washout period. This trial is registered with EudraCT (2009-013400-31) and ClinicalTrials.gov (NCT01068353). Results: Forty-one participants (mean age 72.4 years; 61% men) were randomized to etanercept (n = 20) or placebo (n = 21). Etanercept was well tolerated; 90% of participants (18/20) completed the study compared with 71% (15/21) in the placebo group. Although infections were more common in the etanercept group, there were no serious adverse events or new safety concerns. While there were some interesting trends that favored etanercept, there were no statistically significant changes in cognition, behavior, or global function. Conclusions: This study showed that subcutaneous etanercept (50 mg/wk) was well tolerated in this small group of patients with Alzheimer disease dementia, but a larger more heterogeneous group needs to be tested before recommending its use for broader groups of patients. Classification of evidence: This study shows Class I evidence that weekly subcutaneous etanercept is well tolerated in Alzheimer disease dementia.